A new genus Pontoniopsides, for Pontoniopsis paulae Gore, 1981 (Crustacea: Decapoda: Pontoniinae) - Bruce, A.j. (Zootaxa, 2005)
A new monospecific genus, Pontoniopsides, is designated to include Pontoniopsis paulae Gore, 1981. Pontoniopsides paulae is an echinoid associate occurring in the western Atlantic region. Pontoniopsis now includes only a single species, P. comanthi Borradaile, 1915, a crinoid associated species found throughout the Indo-West Pacific region..